Indonesia’s Economic Growth from 2019 -2021: An Economic Overview Before and During COVID 19 Pandemic - Priana, Wiwin; Sawitri, Dewi Khrisna (Nusantara Science and Technology Proceedings, 2020)
Almost all countries suffer from The Covid 19 pandemic which has emerged since late 2019. This pandemic has greatly impacted the nation's economic growth. Indonesia is also one of many nations with high cases of COVID 19 victims which have experienced the decline of economic growth. Economic growth is also a measure of the economic performance of a nation’s community, the more productive the people in that nation than the higher the economic growth of the nation will be. Economic growth will be obtained from the increase of GDP from year to year. This study has an objective to analyze economic growth in Indonesia which happened before COVID 19 in 2019 until the year 2021 in which this pandemic has still given its economic impact on the nation. Indonesia’s economic growth in 2019 was 5.03%, in 2020 was -2.20% and in 2021 the 2nd Quarter has reached 7.07%. The research method is conducted by analyzing the Report of GDP and Economic growth released by the Central Statistics Agency (BPS). The sample of this research is the year 2019, 2020, and 2021.